2013
DOI: 10.1002/ijc.28353
|View full text |Cite
|
Sign up to set email alerts
|

Fecal immunochemical test accuracy in familial risk colorectal cancer screening

Abstract: There is little information on fecal immunochemical test (FIT) in familial risk colorectal cancer (CRC) screening. Our study assesses FIT accuracy, number needed to scope (NNS) and cost to detect a CRC and an advanced neoplasia (AN) in this setting. We performed a multicentric, prospective, double-blind study of diagnostic tests on individuals with first-degree relatives (FDRs) with CRC submitted to screening colonoscopy. Two stool samples were collected and fecal hemoglobin in the first sample (FIT1) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 38 publications
2
42
0
Order By: Relevance
“…9,10 Second, the diagnostic accuracy of fecal immunochemical test (FIT) is high for CRC and acceptable for AN in this population. 11,12 However, no study, so far, has compared diagnostic accuracy of a quantitative FIT for AN detection between average-risk and familial-risk CRC screening settings. Finally, a randomized, controlled trial comparing FIT with colonoscopy has shown that FIT plus colonoscopy when positive has a similar efficacy as direct colonoscopy to detect AN in FDRs of patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Second, the diagnostic accuracy of fecal immunochemical test (FIT) is high for CRC and acceptable for AN in this population. 11,12 However, no study, so far, has compared diagnostic accuracy of a quantitative FIT for AN detection between average-risk and familial-risk CRC screening settings. Finally, a randomized, controlled trial comparing FIT with colonoscopy has shown that FIT plus colonoscopy when positive has a similar efficacy as direct colonoscopy to detect AN in FDRs of patients with CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study of asymptomatic high-risk patients with a personal history of adenomas/CRC or family history of CRC, sensitivity, specificity, positive predictive value and negative predictive value of single FIT sampling were 80%, 89%, 3% and 99.9% for CRC and 28%, 91%, 24% and 92% for ADA, respectively [53] . High accuracy of FIT was confirmed in a multicenter study among FDRs of CRC patients, in which AUC was 0.96 (95%CI: 0.95-0.98) for CRC and 0.74 (95%CI: 0.66-0.82) for ADA [54] . European guidelines [37] recommend the use of FIT as test of choice for population screening, although gFOBT could be more practicable and affordable than FIT, considering the local labor costs and the mechanism of kit distribution and collection.…”
Section: Familial Crc Screening: What To Domentioning
confidence: 80%
“…First, we have limited our analysis to patients in whom adenomas were detected. We have previously analyzed FIT diagnostic accuracy for colorectal cancer and advanced neoplasia detection (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…These 2 studies aimed to determine the number and the best cutoff point of FIT determinations in average and familial-risk colorectal cancer screening (7,8). A total of 1,317 individuals were recruited, and the most advanced lesion was a colorectal cancer in 9 patients, adenomas in 474 individuals, and nonneoplastic polyps in 179.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation